High commitment performance management: the roles of justice and trust - Farndale, Elaine; Hope Hailey, Veronica; Kelliher, Clare (Emerald Group Publishing Limited, 2011)
Purpose – The purpose of this paper is to explore the relationship between employees' perceptions of a particular subsystem of HRM practices (performance management) and their commitment to the organisation. In addition, the study seeks to examine the mechanisms by which these perceptions translate into employee attitudes and behaviours. Design/methodology/approach – A total of 524 questionnaire responses were collected from four organisations in the UK. Findings – The findings show that the link between employee experiences of high commitment performance management (HCPM) practices and their level of commitment is strongly mediated by related perceptions of organisational justice. In addition, the level of employee trust in the organisation is a significant moderator. Research limitations/implications – This is a cross-sectional study based on self-report data, which limits the reliability of the findings. The findings may also be specific to a particular context. However, the results by company support their generalisability. Practical implications – The findings lead one to believe that it is essential to observe the actual experiences of HCPM practices and outcomes at employee level, and to consider the broader organisational context, if one is to understand their effects on performance. Originality/value – When exploring the impact of high commitment work practices on firm performance, little attention has been paid to the employee perspective: employees ultimately are the recipients of an organisation's HRM practices, and as such their perceptions of these practices affect their attitudes and behaviour in th